(untitled) (Bangladesh Journal of Botany, 2013)
Tetracycline (TC) and ampicillin (AMP) resistant bacteria were identified from both fresh and brackish water shrimp farming system, in Bangladesh. Among 78 isolates from freshwater samples, 14.10, 17.95 and 23.8% were found resistant to TC, AMP and TC plus AMP, respectively. On the other hand, isolates from the brackish water samples, the percentages of TC, AMP and TC plus AMP resistant isolates were 10.25, 12.82 and 15.38, respectively. In freshwater samples, the highest percentage of resistant bacteria was Bacillus sp. (38.9), Pseudomonas sp. (22.2), Staphylococcus sp. (16.7), Acinetobacter sp. (11.1), Brevibacillus sp. (5.5) and Enterobacter sp. (5.5). While in brackish water samples dominant resistant bacteria was Bacillus sp. (50) followed by Pseudomonas sp. (16.7), Acinetobacter sp. (16.7), Enterobacter sp. (8.3) and Microvirgula sp. (8.3). DOI: http://dx.doi.org/10.3329/bjb.v41i2.13449 Bangladesh J. Bot. 41(2): 197-200, 2012 (December)